ANALISIS KEMAMPUAN DARI EKSTRAK ETANOL RUMPUT LAUT Ulva lactuca SEBAGAI ANTIBAKTERI Vibrio sp. DAN KAJIAN FITOKIMIANYA - Metungun, Jakomina; Beruatjaan, Mariana Yerminal; Hitijahubessy, Hendro; Tamher, Endang (Pattimura University, 2023)
An analysis of the antibacterial ability of Vibrio sp. has been carried out from the ethanol extract of Ulva lactuca seaweed and its phytochemical study. Analysis of the antibacterial ability of Vibrio sp. using the disk diffusion method was the main thing carried out in this research, then the extract yield was calculated from the maceration process of Ulva lactuca seaweed, as well as phytochemical analysis to support the antibacterial ability of Ulva lactuca seaweed against the bacteria Vibrio sp. The results of the extraction of Ulva lactuca seaweed with ethanol solvent obtained a yield of 3.67%. The results showed a moderate antibacterial activity of Vibrio sp. from Ulva lactuca seaweed extract at a concentration of 100% was 17.3 mm. Weak antibacterial activity was at a concentration of 75% of 12.525 mm and extracts below a concentration of 75% did not have inhibitory power against Vibrio sp bacteria. Phytochemical studies of Ulva lactuca seaweed found secondary metabolite compounds in the form of alkaloids, flavonoids, steroids, tannins and saponins. Based on the results of this research, it is hoped that the antibacterial ability of Vibrio sp. can be further investigated from ethanol extract of Ulva lactuca seaweed in vivo.